Early autism therapy: A review - Solano-Dazzarola, Paula Andrea (2023)
Background: Autism or Autism Spectrum Disorder is considered a behavioral syndrome that compromises motor and intellectual development, leading to predominant difficulties in executive functions that significantly impact the daily development of the human being. Objective: The objective of this topic review is to identify how patients with autism spectrum disorder can function within society through early intervention of the predominant signs and symptoms of autism. Materials and methods: A bibliographic review was carried out in databases, using search equations to filter documents between 2010-2021 that contain information on autistic patients, early interventions, reintegration into society and their abilities. Results: Autism is a pathology diagnosed mainly at an early age, so the intervention must be timely, individualized and adapted to the needs and objectives of each patient in order to intervene in the predominant aspects of the patient and facilitate their integration and performance. Social. Conclusions: Individuals with autism must be treated, above their condition of disability as people, which entails ethical values and respect for their dignity that must guide the entire intervention. The diagnosis carries with it multiple stigmas to which the general population should be made aware, implying that despite the difficulties present in development, they can become proficient in various activities taking into account the severity of the symptoms and the effectiveness of early intervention.